2002
DOI: 10.1046/j.1474-8673.2002.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of catecholamine release in the isolated adrenal glands of SHR and WKY rats

Abstract: 1 The present study was designed to investigate the secretion of catecholamines (CA) evoked by stimulation of cholinergic receptors and membrane depolarization from the isolated perfused adrenal gland of spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto rats (WKYR) at adult age. 2 The wet weight of adrenal gland in SHR was greater than that in WKYR. The CA releasing responses evoked by acetylcholine (5.32 x 10-3 m), and high potassium (5.6 x 10-2 m), a membrane depolarizer, were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 49 publications
3
13
1
Order By: Relevance
“…1-3). This corroborates the observation of Lim et al (2002), who in the perfused intact adrenal gland observed that stimulation with ACh or K ϩ enhanced more the catecholamine present in 4-min perfusate samples of SHRs, as compared with control rats. However, in such a study using the intact gland, the slow perfusion rate and the low …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…1-3). This corroborates the observation of Lim et al (2002), who in the perfused intact adrenal gland observed that stimulation with ACh or K ϩ enhanced more the catecholamine present in 4-min perfusate samples of SHRs, as compared with control rats. However, in such a study using the intact gland, the slow perfusion rate and the low …”
Section: Discussionsupporting
confidence: 78%
“…A recent study on catecholamine release from intact perfused rat adrenal glands indicates that release stimulated by acetylcholine (ACh), the physiological neurotransmitter at the adrenal medulla splanchnic nerve-chromaffin cell synapse (Feldberg et al, 1934), or by high K ϩ concentrations (K ϩ ), is higher in adrenals from SHR, as compared with the responses obtained in control normotensive rats (Lim et al, 2002). However, in this study, secretion was assessed upon collection of 4-min perfusate samples, with a poor temporal resolution to study a fast secretory event such as exocytosis of chromaffin cells (Neher, 1998).…”
mentioning
confidence: 99%
“…Enhanced response to stimulation of SHR adrenals isolated in vitro was found, electrical stimulation increased the norepinephrine output from the SHR adrenals significantly greater than from those of the normotensive WKY rats (Nagayama et al 1999). Stimulation of cholinergic receptors of isolated in vitro adrenals of the SHR produced a more prominent catecholamine release than from those of the WKY rats (Lim et al 2002). The role of hyperactivity of the sympathetic adrenal system in sustained hypertension has been confirmed by experiments with its inhibition; long-term inhibition of the sympathetic adrenal system in young but mature SHR by rilmenidine, a centrally active antihypertensive agent interacting with imidazoline receptors, not only reduced blood pressure to normotensive levels, but had beneficial effects on cardiovascular structure, potentially reducing risk factors for Figure 6 Gene expression in the WAG (white columns) and the ISIAH (black columns) rat strains (meanG S.E.M., nZ6-8 in each group).…”
Section: Discussionmentioning
confidence: 84%
“…Nonetheless, the lack of expression of Ca V 1.3 42 channels apparently does not cause major functional alterations: WKY rats are normotensive and display cardiovascular responses (transient elevation of blood pressure and tachycardia) to conditioned emotional stimuli (38), and WKY CCs secrete catecholamines normally (17). It remains to be determined whether or not WKY/SHR CCs fire spontaneous action potentials at lower frequency than Wistar CCs.…”
Section: Effects Of Nifedipine and (ϫ)Bay K 8644 On I Ca Componentsmentioning
confidence: 98%